Common Health Problems Among Agricultural Workers in A Selected Rural Area of Mymensingh, Bangladesh - Hasan, AHM; Hossain, Md Tufael; Begum, Maksuda; Islam, Md Shahidul; Alam, Fakir Sameul (Community Based Medical Journal, 2022)
This cross-sectional descriptive study was conducted in Churkhai village of Bhavokhali union during December 2018 to find out common health problems among 200 agricultural workers in a selected rural area of Mymensingh as a part of Residential Field Site Training by 3rd year MBBS students session 2016-17. 63 percent of population lives in rural area. Agricultural workers have illnesses common to general population. Moreover socioeconomic and work condition poses extra burden. The study was carried out on 200 agricultural workers who were selected purposively. Data were collected on a predesigned questionnaire by face to face interviewing agricultural workers. Data analysis was done by SPSS version 20.0. Age distribution of respondents ranged from 19 years to 80 years; mean age 46.53 years and standard deviation 14.891 years. Males were predominant (male: female ratio 506.06: 100. Majority of them (57.50%) were literate. Most of them (65.00%) belonged to middle class family. More than half (55.00%) of agricultural workers were suffering from illness. Respiratory illnesses 16.00% were predominant followed by skin disease 10.50%, gastrointestinal disease 6.50%, conjunctivitis 6.00%, arthritis 6.00%, hypertension 6.00%, diabetes mellitus 5.00%, anemia 4.50% and hearing loss 0.50%. In summer heat exhaustion (14.50%) was predominant followed by heat syncope (10.00%. In rainy season ARI (12.00%) was predominant followed by diarrheal diseases (10.50%). In winter mild hypothermia (27.00%) was predominant followed by ARI (4.50%). In recall of last 1 year the important events were crop loss 12.50%, damage to house 10.00%, and unemployment 2.50%. There was no case of anthrax and bird flu. Prevalence of occupational accidents was 5.00%. which includes fall from height 0.50%, heavy object fallen on body 1%, domestic fire 1%, electrocution in house 1%, electrocution by power pump 0.50%, cattle hitting by horn 0.50% and accidental insecticide poisoning 0.5%. Most of the injury occurred in the current week. Majority of the workers (66.50%) had partial tetanus toxoid immunization. Morbidity in this study was better than several studies conducted in Bangladesh and India. By knowing health problems we can give health care to agricultural workers which will prevent diseases and illnesses of them, prolong their healthy life, promote their health and efficiency. CBMJ 2022 July: vol. 11 no. 02 P: 125-130